SEDIMENTATION IMPACT ON CAPACITY AND MORPHOLOGY CHANGES ON BENDUNG RIVER OF PALEMBANG CITY - Ayunda Prima, Priseyola
Bendung River is one of the rivers in Palembang City that experiences overflowing when the rainy season occurs. This river length is 5.47 km, and its basin area is 18.38 km2. The flood that occurred in the area around the Sungai Bendung has caused material and non-material losses. The flood that occurred was due to the capacity of the Bendung River not being able to accommodate the flood discharge. In addition, backwater from the Musi River which is the estuary of the Bendung River is also one of the causes of flooding. The reduced capacity of the Bendung River is caused by sedimentation that occurs almost along with the river flow. The research method in this study is sedimentation modeling using HEC-RAS 6.1 1D using cross-sectional data from upstream to downstream of the Bendung River. In this study, primary data was collected, namely floating sediment samples and base sediments. This study aims to determine the amount of sediment in the Bendung River at the time of flooding for a definite return period, analyze the influence of remaining sediment on changes in river morphology and capacity of the Bendung River in Palembang City and provide recommendations for normalization locations on the Bendung River. From the results of this study, it was found that sediment affects the capacity of the Bendung River and causes vertical morphological changes, both in aggradation and degradation. The location that must be normalized on the Bendung River every year is upstream to the middle part of the Bendung River.